A vesicular stomatitis virus-based African swine fever vaccine prototype effectively induced robust immune responses in mice following a single-dose immunization - Ma, Yunyun; Shao, Junjun; Liu, Wei; Gao, Shandian; Peng, Decai; Miao, Chun; Yang, Sicheng; Hou, Zhuo; Zhou, Guangqing; Qi, Xuefeng; Chang, Huiyun (Frontiers in Microbiology, 2024)
Introduction: African swine fever (ASF) is a highly contagious hemorrhage fever disease in pigs caused by African swine fever virus (ASFV). It is very difficult to control and prevent ASF outbreaks due to the absence of safety and effective vaccines.In order to develop a safe and effective ASF vaccine for control and prevention of ASF, two ASFV recombinant VSV lived vector vaccine prototypes, containing the gene of p72, and a chimera of p30 and p54, have been developed based on the replication-competent vesicular stomatitis virus (VSV), named VSV-p72 and VSV-p35. The immune potency of VSV-p72 or VSV-p35 alone, and the combination was evaluated in BALB/c mice via intramuscularly and intranasally vaccination.The results indicated that whether administration alone or combination of two vaccine prototypes showed acceptable safety in mice, more importantly, it induced high level specific antibodies against p72, p30 and p54 of ASFV and strong cellular immune response in 28 days after vaccination. The sera from mice vaccinated with the vaccine prototypes significantly inhibited ASFV to infect PAMs in vitro. Most notably, the immunized sera from mixture of VSV-p35 and VSV-p72 inhibited ASFV to infect PAMs with an inhibition rate up to 78.58%.Overall, our findings suggested that ASFV recombinant VSV lived vector vaccine prototypes may become a promising candidate vaccines for control and prevention of ASF.